Establishment of Quantitative PCR Assays for Active Long Interspersed Nuclear Element-1 Subfamilies in Mice and Applications to the Analysis of Aging-Associated Retrotransposition - Kuroki, Ryota; Murata, Yui; Fuke, Satoshi; Nakachi, Yutaka; Nakashima, Jun; Kujoth, Gregory C.; Prolla, Tomas A.; Bundo, Miki; Kato, Tadafumi; Iwamoto, Kazuya (Frontiers in Genetics, 2020)
The retrotransposon LINE-1 can autonomously increase its copy number within a host genome through the retrotransposition process. LINE-1 is active in the germline and in neural progenitor cells, and its somatic retrotransposition activity has a broad impact on neural development and susceptibility to neuropsychiatric disorders. The method to quantify the genomic copy number of LINE-1 would be important in unraveling the role of retrotransposition, especially in the brain. However, because of the species-specific evolution of LINE-1 sequences, methods for quantifying the copy number should be independently developed. Here, we developed a qPCR assay to measure the copy number of active LINE-1 subfamilies in mice. Using the assay, we investigated aging-associated alterations of LINE-1 copy number in several brain regions in wild-type mice and Polg+/D257A mice as a model for accelerated aging. We found that aged Polg+/D257A mice showed higher levels of the type GfII LINE-1 in the basal ganglia than the wild-type mice did, highlighting the importance of assays that focus on an individual active LINE-1 subfamily.